2019
DOI: 10.1038/s41561-019-0368-9
|View full text |Cite
|
Sign up to set email alerts
|

Highly heterogeneous depleted mantle recorded in the lower oceanic crust

Abstract: The Earth's mantle is heterogeneous as a result of early planetary differentiation and subsequent crustal recycling during plate tectonics. Radiogenic isotope signatures of midocean ridge basalts have been used for decades to map mantle composition, defining the depleted mantle end member. These lavas, however, homogenize via magma mixing and may not capture the full chemical variability of their mantle source. Here we show that the depleted mantle is significantly more heterogeneous than previously inferred f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 57 publications
1
36
1
Order By: Relevance
“…Given that plagioclase is able to record the effects of crystallization from distinct melts present at small scales, the observed range of trace element and isotopic heterogeneity in megacrysts is arguably a more realistic indication of the heterogeneity of mantle melts as one may sample them in the upper mantle compared to the local diversity of erupted lavas, both because of mixing during transport. This is consistent with the observed patterns seen in lower crustal gabbros (Coogan, 2014;Lambart et al, 2019) and olivine-hosted inclusions (e.g., Jones et al, 2019).…”
Section: Magmatic History Recorded In Plagioclasesupporting
confidence: 91%
See 2 more Smart Citations
“…Given that plagioclase is able to record the effects of crystallization from distinct melts present at small scales, the observed range of trace element and isotopic heterogeneity in megacrysts is arguably a more realistic indication of the heterogeneity of mantle melts as one may sample them in the upper mantle compared to the local diversity of erupted lavas, both because of mixing during transport. This is consistent with the observed patterns seen in lower crustal gabbros (Coogan, 2014;Lambart et al, 2019) and olivine-hosted inclusions (e.g., Jones et al, 2019).…”
Section: Magmatic History Recorded In Plagioclasesupporting
confidence: 91%
“…Unlike phyric MORBs containing plagioclase with complex major element zonation patterns reported at some locations (Kuo & Kirkpatrick, 1982;Lambart et al, 2019;Meyer & Shibata, 1990), the phenocrysts from the PUB lavas from this study have homogeneous cores with occasional thin lower anorthite rims (Figure 3). Plagioclase megacrysts with unzoned cores have been reported at several other locations (Sasha Seamount in Lamont Seamount chain; Allan et al, 1989;Siqueiros Transform, Batiza et al, 1977;ODP Hole 648B, Serocki volcano, Mid-Atlantic Ridge, Costa et al, 2010: Gorda Ridge, Nielsen et al, 1995.…”
Section: Correlation Of Phenocryst Major and Trace Elementscontrasting
confidence: 54%
See 1 more Smart Citation
“…This diagram also shows a key feature of our model, in that the sub-ridge mantle contains streaks and/or blebs of pyroxenitic material set in a peridotite matrix. Melt mixing and homogenisation is believed to occur in sub-ridge magma storage regions as recent studies have shown that the isotopic heterogeneity of melt entering the crust beneath oceanic spreading centres is very large (Lambart et al, 2019 Hart, 2005), as their estimate for the trace-element composition of the average DMM was not able to reproduce the highly depleted nature of D-MORBs from the GSC.…”
Section: Figuresmentioning
confidence: 99%
“…The clinopyroxene and whole rock samples analyzed herein are generally indistinguishable from the Hole 735B average, except sample MS20-10 (ε 143 Nd = +6.8) which is the least radiogenic so far measured but remains well within the range of heterogeneity observed along the SWIR (Figure 7). The preservation of extreme isotopic heterogeneity in oceanic mantle between constituent phases and across small length is increasingly being recognized as a common phenomenon (Burton et al, 2012;Lambart et al, 2019). This is not an unexpected results given the depleted mantle represents a mixture of materials at different stages in their evolution, and is therefore unlikely to be a isotopically homogeneous (e.g., Salters and Stracke, 2004).…”
Section: Radiogenic Nd Isotope Variabilitymentioning
confidence: 99%